Firm Growth, Institutions and Structural Transformation - Magnus Henrekson; Dan Johansson (Research Institute of Industrial Economics (IFN), 2010)
This essay argues that the economic contribution of certain firms be they small, young or rapidly growing has to be understood in a broader context of creative destruction. Growth of some firms requires contraction and exit of some other firms to free up resources that can be reallocated to expanding firms. Entry and expansion are flip sides to exit and contraction and the process through which the factors of production are put into different use defines structural transformation. We analyze institutions and policies conducive to structural transformation, in particular the expansion of high-growth firms (HGFs), since they have empirically been shown to contribute disproportionately to economic development. Firm growth is viewed as resulting from the continuous discovery and use of productive knowledge. Rapid firm growth requires a set of economic actors with complementary competencies that work together to identify and commercialize novel business ideas. The institutional framework determines the incentives for these individuals to acquire and utilize knowledge. We identify a number of institutions that encourage the creation of HGFs and promote structural transformation. In particular, our analysis points to the key roles played by tax structures, labor market regulation, and the contestability of service markets. Even in advanced economies, there is a large untapped economic potential which can be unleashed by institutional changes, such as the opening up of closed markets for entrepreneurial competition. However, there is no quick-fix that will boost the frequency of HGFs and structural transformation. Our analysis suggests that policymakers need to adopt a broad approach and implement a wide array of complementary institutional reforms to increase the prevalence of HGFs and to facilitate structural transformation.
Keywords: D21; L25; M13; O10; O40; 330; Entrepreneurship; Firm growth; Gazelles; High-growth firms; High-impact firms; Institutions; Job creation; Rapidly growing firms; Unternehmenswachstum; Schumpeterismus; Strukturwandel; Institutioneller Wandel; Innovation; Wissensmanagement